Counseling on health protocols in public transport for kopamas drivers in Bandung City - Manurung, Rosida Tiurma; Pattipawaej, Olga; Ratnadewi, Ratnadewi (Universitas Muhammadiyah Magelang, 2021)
In the era of adapting new habits after the Covid-19 pandemic, especially public transportation, it is necessary to provide health protocol counseling to kopamas drivers. This counseling is important considering the problem of the spread of Covid-19 in Bandung is still high. The purpose of this activity is to provide counseling on the application of health protocols to kopamas drivers, establish concern for others, especially the community in the campus environment; prevent the wider spread of Covid-19; and develop an attitude of concern for environmental health. This activity was carried out at the house of the chairman of RW 01 Sukagalih Village. The kopamas drivers were accompanied directly by a team of extension workers. The pocket books on health protocols, stickers, masks and basic necessities were distributed to kopamas drivers during counseling. This service generates understanding for kopamas drivers and is expected to be able to educate kopamas passengers.